PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KEPEMILIKAN INSTITUSIONAL - Roy Hutapea; Andri Prastiwi (Diponegoro Journal of Accounting, 2013)
This study aimed to determine the effect of disclosure of Corporate Social Responsibility and dimensions disclosure of Corporate Social Responsibility (CSR) towards institutional ownership of the company. The dimensions of CSR disclosure following indicators Golden Hope Plantation Berhad (GHPB) which consists of four categories: Dimensions with employees, involvement with community,.products,.and.environment..Institutional.ownership.of.the.company.seen.by.shares.held.in.a.company.institution. This study used the entire population of companies listed on the Stock Exchange (Indonesia Stock Exchange) in 2010-2012. Based on purposive sampling method obtained 36 samples of firms with data sources such as company annual reports. Analysis of the data using content analysis, prepared by the classical assumption, and then testing the hypothesis using multiple linear regression method.The results showed that only the disclosure of CSR entirely, CSR dimensions and product dimensions employees are positive and significant impact on institutional ownership of the company. While the dimensions of CSR and CSR community involvement with the environmental dimension is not positive and significant impact on institutional ownership. The results are generally in accordance with the results of previous studies regarding the disclosure of Corporate Social Responsibility (CSR) and its relationship with institutional..ownership.